Research on accelerating the recycling efficiency of waste batteries for new energy vehicles based on a stochastic evolutionary game model - Xiangyu Mao; Ying Wang; Yichong Mao; Haohao Song (Scientific Reports)
Abstract Although the rapid development of new energy vehicles (NEV) has contributed greatly to China’s carbon emission reduction, it has also brought about a problem that needs to be solved, namely the effective recycling of waste batteries. Existing recycling of waste batteries is plagued by a series of problems such as a single recycling channel, inconsistent recycling standards, lack of recycling technology, rampant irregular recycling enterprises, and low consumer participation. Meanwhile, due to the immaturity of the recycling market, the lack of clarity of existing regulations, and the lack of supervision and management, the above problems are becoming more and more serious. Therefore, to solve these problems, this paper constructs a four-party stochastic evolutionary game model including government regulators, NEV enterprises, third-party recycling enterprises, and consumers. Focus on analyzing the impact of relevant parameters on the choice of strategies by participants, and put forward proposed countermeasures to promote the effective recycling of waste batteries based on the conclusions.